Generalizing figural patterns with students of 8 and 9 years old: an interpretation of the semiotic means of objectification mobilized - Lasprilla Herrera, Adriana; Camelo Bustos, Francisco Javier (Colombian Applied Linguistics Journal, 2012)
This paper reports the semiotic objectification means that arose among 7 and 8 year-old children from a school in Bogota D.C., Colombia in a math class, when they addressed a generalization task of figural patterns as a process of meaning production. The analysis was conducted according to the cultural theory of objectification (Radford, 2008), particularly the layers of generality and the semiotic means of objectification developed by the student it. Found that students in this study identified the semiotic means employed by Radford (2010) and were located in a layer of factual generality.